Proceedings of the 2013 International Academic Workshop on Social Science (IAW-SC-13) 2013
DOI: 10.2991/iaw-sc.2013.122
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Regime and Malaria Cases in Orlu Area of Imo State Nigeria

Abstract: The earth's climate is becoming increasingly warmer, most likely due to increasing greenhouse gas emissions. Climate variation is driven by uneven distribution of solar heating, the individual responses of the atmosphere, oceans and land surface, the interactions between these and the physical characteristics of the regions. Climate, more especially temperature has a strong and direct influence on development, reproduction and survival of tropical insects such as mosquitoes. Insect population growth potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, among the sub-Saharan African countries, Nigeria has the highest share of the global burden of malaria disease [3]. More than 95% of the malaria cases in Nigeria are caused by P. falciparum [10][11][12], mostly occurring in children under the age of 5 years [3,10,12]. At present almost more than 70% of the Nigerian population live in endemic areas [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the sub-Saharan African countries, Nigeria has the highest share of the global burden of malaria disease [3]. More than 95% of the malaria cases in Nigeria are caused by P. falciparum [10][11][12], mostly occurring in children under the age of 5 years [3,10,12]. At present almost more than 70% of the Nigerian population live in endemic areas [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A challenge in studying malaria risk in Nigeria is the heterogeneity of the prevalence, which is attributed to high variability in climate conditions as well as the landscape [2,16]. Few published studies in Nigeria have linked malaria prevalence to several influencing factors, including climate and environmental conditions [2,10,11,13,15,[17][18][19][20], socioeconomic factors [15,[21][22][23], geographical factors [10,[13][14][15]18,24], and control strategies as well as prevalence of other febrile illnesses [22,[25][26][27]. Additionally, several authors in other malaria endemic countries have investigated the correlation between malaria and important meteorological variables as observed in Venezuela [6][7][8][9], in Zimbabwe [28], in Zambia [29,30], in Côte D'Ivoire [31], in Ghana [32], in Burundi [33], in Ethiopia [34,35] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Different research works have been conducted to evaluate the impact of temperature on malaria incidence. Studies carried out in Kebbi State by [18]; in Orlu, Imo State by [19]; in Enugu State by [20]; in Plateau State by [21]; in Abuja, Nigeria by [22] revealed that temperature had a significant impact on malaria transmission whereas [23] reported no significant impact.…”
Section: Introductionmentioning
confidence: 99%